New skillsets for future science, technology, engineering and mathematics (STEM) library workforce (2019)
The advent of new technologies makes it imperative for library staff to continually improve their skills, to meet user needs and for excellent service delivery. As a result, training and retraining of staff becomes top priority. With research in Science, Technology, Engineering and Mathematics (STEM) on the increase, libraries serving this population find that the rate of training and the skills needed in anticipation, for the workforce has to increase for them to meet future expectations of their users. This study was conducted to find out the perceived needs of the workforce (librarians and support staff) in STEM libraries on what skills they need for future service delivery. Questionnaires and Interviews were used for data collection. 70 librarians and library officers formed the target population of the study, of which 40 responded. The findings showed that respondents perceived that having a good grasp of future technologies, constant updating of literacy and digital skills as well as training in computer programming and design are absolutely essential skill sets for the future STEM library workforce. The future STEM librarian will need specialized clientele management training for effective service delivery. Formal training in use of computer assisted tools such as Artificial intelligence, immersive technology and others will be imperative for the future STEM workforce. Constant re-skilling and acquisition of critical thinking and computer programming skills will be absolutely essential moving forward.